Electoral Incentives and Legislative Organization: An Examination of Committee Autonomy in U.S. State Legislatures. (September 2014) - Bagashka, Tanya; Clark, Jennifer Hayes
Abstract: We investigate the relationship between electoral institutions and committee autonomy in the context of U.S. state legislatures. The distributive theories of legislative organization suggest that electoral rules that make personal reputations more important motivate legislators to decentralize power and enhance committee autonomy to be able to target particularistic goods to their local constituencies. We argue that the distributive theories have direct implications for the relationship between candidate selection procedures and committee autonomy. The need to reach out to a large number of voters and to amass significant financial resources in states with more inclusive candidate selection procedures such as the open primary makes representatives more dependent on special interests, which is conducive to legislative particularism and committee autonomy. We take advantage of the great variation across the American states to investigate the effects of candidate selection procedures, a factor neglected in the previous literature. Examining 24 state legislatures from 1955 to 1995, we find that the inclusiveness of the selectorate, or the body electing candidates, has a significant effect on committee autonomy with more inclusive primary elections leading to more autonomous committee systems. By contrast, however, term limits were not a significant predictor of committee autonomy. This contributes to our understanding of how legislators amend institutional arrangements to achieve their electoral goals.